Quality of care at before and after school care programmes : a case study on regulatable features, programme activities, child and parent perspectives - Goh, Lay Lian. (2008)
This study examines children's experiences at the Lakeside Before and After School Care (BASC) Programme. Regulatable features such as staff-child ratio, total enrolment and staff education were assessed via the head's report. Observers recorded positive/neutral and negative staff-child interactions, and rated activities in terms of flexibility and age-appropriateness. There was a positive association between staff-child ratio and staff education and staff-child interactions. Observers reported more frequent positive/neutral than negative interactions between staff and children. Lower primary children (Primary One to Three) were reported to have more frequent positive/neutral interactions than upper primary children (Primary Four to Six). Observers rated programmes as flexible and age-appropriate. These regulatable and observed features were examined in relation to children's (N=129) and parents' (N=96) perceptions of programme psychosocial climate. Children's reports of overall climate, emotional support from staff, and privacy/autonomy were positively related to programme features. Children from the upper primary reported more positive programme climate than children from the lower primary. The wide range of activities offered and low staff-child ratio appeared to have contributed to positive programme climate. Parents' reports of programme climate were also related to children's reports. Parents of lower primary children reported more positive programme climate than parents of upper primary children. This study suggests that quality programme is related to regulatable and programme features.